Kettlebell en la potencia de las extremidades inferiores en jóvenes - Lema Vargas, Jonathan Alexander (2025)
This study aimed to analyze the effect of a kettlebell training program on the development of lower limb power in young soccer players from the Menothy Vargas Soccer School, located in Macas, Ecuador. A quantitative approach was used, applying a quasi-experimental pretest–posttest design and the vertical jump test through the My Jump 2 mobile application, scientifically validated for measuring muscular power. The eight-week intervention consisted of structured sessions focused on promoting triple joint extension (hip, knee, and ankle). The results showed significant improvements in flight time (+13.29 %), take-off velocity (+13.33 %), and mechanical power (+16.56 %), confirming the effectiveness of kettlebell training as a functional, economical, and safe alternative to enhance the physical performance of young soccer players. It is concluded that this methodology is an efficient tool to optimize lower limb explosive capacity and is recommended for systematic inclusion in youth physical conditioning programs.